Strategi Komunikasi Pemasaran Produk Perkreditan PT. BPR Ukabima Grazia - Suwirya Tjandra; Juhaini (Syntax Corporation, 2023)
The formulation of the problem in this study is none other than how the communication strategy carried out by the management of BPR Grazia in facing competition from its competitors. This research was conducted with the intention of analyzing marketing communication strategies in an effort to improve the marketing of BPR Grazia Credit products. The method used is qualitative descriptive with interview techniques and field observations of the Three informants determined through purposive sampling techniques of Commissioners, Branch Heads, Executive Officers and 2 Marketing Staff of BPR Grazia as key informants. With this, researchers try to discuss the efforts that have been and are being carried out by BPR Grazia in its efforts to market banking service products to the wider community, marketing strategies that are applied by the small BPR Grazia so that it can continue to 'survive' and continue to develop into a large and solid bank. From the results of the research analysis that has been carried out, it can be concluded that the marketing communication element where the outline consists of Executive Officers, sales promotion, public relations, personal selling and direct and internet marketing has been carried out by BPR. Overall, BPR Grazia has implemented a good communication strategy to increase sales of its credit products in order to achieve the Bank's Business Plan (RBB) target which has been prepared and approved by the Financial Services Authorit.